Making Space: Racialized Organizations and Student of Color Groups at U.S. Colleges and Universities. Issue 3 (July 2022) - Schachle, Jessica L.; Coley, Jonathan S.
A growing body of scholarship demonstrates the positive role that Asian, Black, Latinx, and Native American student groups play in the lives of students of color. Yet, we currently know little about the prevalence of student of color organizations and the characteristics of colleges and universities that are home to one or more student of color organizations. Analyzing our original database of officially recognized student of color organizations across 1, 910 four-year, not-for-profit U.S. colleges and universities, we find that although a slight majority of U.S. colleges and universities are home to Black student groups, most U.S. colleges and universities lack Asian, Latinx, and Native American student groups. Drawing on recent insights from racialized organization theory, and employing logistic and Poisson regression, we also show that schools that have higher percentages of students of color, offer ethnic studies majors, and maintain centers devoted to issues of racial diversity, equity, and inclusion exhibit higher odds of having at least one student of color organization. A similar set of factors is associated with the overall number of students of color organizations at any given school. Our study advances scholarship on student of color mobilization within higher education and sheds light on issues of unequal access to student organizations more generally.